A 5-year retrospective analysis of necrotizing fasciitis – A single center experiences - Kiralj, Aleksandar I; Janjić, Zlata; Nikolić, Jelena; Markov, Borislav; Marinković, Marija (Vojnosanitetski pregled, 2015)
Background/Aim. Necrotizing fasciitis (NF) is usually an acute infection of superficial fascia with rapid progression in around soft tissue. If not promptly recognized and aggressively treated NF usualy leads to sepsis and multiorgan failure with fatal outcome, thus early diagnosis and prompt surgical treatment are crucial for healing of these patients. The aim of this article was to evaluate the clinical presentation of all patients with acute NF diagnosed and treated in surgical clinics of Clinical Center of Vojvodina, Novi Sad, Serbia. Methods. The medical records of patients treated for acute NF localized on a different parts of the body in Clinical Center of Vojvodina, Novi Sad, Serbia, during a 5-year period (from January 2008 to December 2012) were retrospectively evaluated. This study enrolled patients admitted via Emergency Center of Vojvodina with the diagnosis of acute NF either as the primary diagnosis or with the diagnosis at discharge after surgical treatment.  Results. During a 5-year period there were 216 patients with final diagnosis of acute NF. Most of our patients (140 – 64.81%) were admitted with the initial diagnosis of cellulitis, abscesses, phlegmons or sepsis. Unfortunately, the clinical symptoms of acute NF were atypical at time of initial examination. Pain and swelling of the affected localization were the most presented bias of symptoms (183 – 84.72%). The majority of our patients were male (164 – 75.92%). Among the 216 patients, the most common pre-existing single factor was drug abuse (39 – 18.05%), followed by obesity (38 – 17.59%) and diabetes mellitus (31 – 14.35%). Trauma was most common etiological factor (22 – 10.8%) in infected wounds, followed by abdominal (15 – 6.94%) and orthopedic (11 – 5.09%) surgical intervention. In the present study idiopathic acute NF was diagnosed in 22 (10.18%) patients and more than one etiological factor were diagnosed in 20 (9.25%) patients. The majority of our patients had type I acute NF (172 – 79.62%) with Streptococcal species as the most common microorganism (125 – 71.02%). The most common localization was an extremity (151 – 69.90%). The minority of our patients had head and neck localization of infection (7 – 3.24%). Surgical treatment was performed in all the patients and most of them (183 – 84.72%) received the first surgery within 24 h. Other patients (23 – 10.64%) received operation after stabilization of general status or after getting the diagnosis of acute NF (unclear diagnosis on admission). During hospitalization, the most common complication among our patients was sepsis (156 – 72.22%). The mortality rate was 14.35%. Conclusion. Acute NF is a rare but very difficult and sometimes life-threatening disease of superficial fascia and around soft tissue. If acute NF is suspected, early radical excision of all the affected tissue with exploration and excision of superficial fascia with pathological and microbiological assessment are most significant for treatment. Appropriate antibiotics and intensive care setting to manage other organ failure of NF are recommended at the same time with surgery.
Keywords: fasciitis; necrotizing; risk factors; surgical procedures; operative; serbia